The jungle books - Kipling, Rudyard, 1865-1936.; Karlin, Daniel, 1953- (Harmondsworth, Middlesex, England ; New York, N.Y., U.S.A. : Penguin Books, 1987)
Presents the adventures of Mowgli, a boy reared by a pack of wolves and the wild animals of the jungle. Also includes other short stories set in India.
Includes bibliographical references.
Keywords: Mowgli (Fictitious character) -- Fiction; Adventure stories, English; Jungle animals -- Fiction; Feral children -- Fiction; Boys -- Fiction; Jungles -- Fiction; Animals -- Fiction; Short stories; India -- Fiction; India -- Fiction